PENGARUH JENIS DAN KOMPOSISI PEREKAT TERHADAP KUALITAS BRIKET BATUBARA MUDA - Jahiding M.; Mashuni .; E.S. Hasan; Gangganora A.S. (Universitas Halu Oleo, 2014)
It has been tested qualitybrown coal powderusingproximate analysisandcalorific value analysis. Powder and briquettes of brown coalmade with jatropha seed starch, cassavastarch, andstarchas anbinder.Powder and briquettes of brown coalwith varied jatropha seedstarch, cassavastarchandstarchcompositionof5%, 10% and15% of thetotalmass sample. Size of brown coalparticle used by 60 mesh. Samplesprinted in cylindrical mold with diameter 1.52cm and acompactionpressureof100kg/cm2. Testing the quality of brown coalpowderinclude determiningparameters: moisture content, volatile matter, ash content, fixed carbon and calorific value. Testing the quality of brown coal briquettes includedensity,suluttime, andtime of flame. The results showed caloric testing of mix brown coal powder with jatropha seed starch, cassava starch and starch binder with composition 5%, 10% and 15% obtained calorific value between 5573.233 kcal/kg until 5971.028 kcal/kg. Highest calorific value is at cassava starch with composition 10%.